Um estudo sobre o consumo de produtos de beleza e higiene capilar pelas mulheres de baixa renda da região metropolitana de Salvador - VEIGA, Fernanda Dantas (2014)
The purchasing power of low-income population in Brazil has shown significant growth mainly from the last decade. This fact aroused the interest of entrepreneurs and researchers in the area of marketing to understand more deeply the behavior of consumption in this portion of the population. Despite the increase in power consumption, the household budget of the population base of the pyramid is restricted, limiting the consumption of certain products. But even with financial constraints, this portion of society is a major consumer of products that can be considered superfluous, as is the case of consumption of beauty products. The objective of this work is to identify the real reasons why low-income women to consume regular beauty products and hair care, even having basic and most urgent needs to meet. This research is qualitative and exploratory approach uses the theory of Means-End Chains as a research strategy and will apply the Laddering technique that makes use of in-depth interviews to collect primary data.